1977
DOI: 10.3109/00365527709181707
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Macroamylasemia and the Diagnostic Value of the Amylase to Creatinine Clearance Ratio in Patients with Elevated Serum Amylase Activity

Abstract: 190 patients with elevated serum amylase levels were tested for macroamylasemia and the amylase to creatinine clearance ratio. Macroamylasemia was found in 3 patients. In these patients macroamylasemia persisted after the total activity of serum amylase had fallen to nearly normal levels. The Cam/Ccr-ratios were determined 14 times in the 3 macroamylasemic patients. Only one of the 14 values was clearly less than 1%. Cam/Ccr-ratios above 4% were found in 83 patients. In 56 of them the diagnosis of acute pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…While some confirmed the value of this investigation (2 -5 ), others demonstrated that a normal CAm/CCr does not exclude acute pancreatitis (6 -8 ) as has been previously sug gested (9). Furthermore, other groups question the specificity of the CAm/Ccr> reporting raised values in several conditions other than pancre atitis: bums and ketoacidosis (10), acute duo denal perforation (11), renal insufficiency (6,8,(12)(13)(14) and thoracic operation (15,16).…”
Section: Warshaw and Fullermentioning
confidence: 99%
“…While some confirmed the value of this investigation (2 -5 ), others demonstrated that a normal CAm/CCr does not exclude acute pancreatitis (6 -8 ) as has been previously sug gested (9). Furthermore, other groups question the specificity of the CAm/Ccr> reporting raised values in several conditions other than pancre atitis: bums and ketoacidosis (10), acute duo denal perforation (11), renal insufficiency (6,8,(12)(13)(14) and thoracic operation (15,16).…”
Section: Warshaw and Fullermentioning
confidence: 99%
“…An amylase clearance/creatinine clear ance (Cam/Ccr) ratio below 1 % would strengthen suspicion of underlying macro amylasemia [44], Indeed, the inability of macrocomplexes to pass through the glomerular filter induces a low Cam/Ccr ratio, at least in Type 1. However, Cam/Ccr failed to be sensitive and specific in many conditions [45], So, a Cam/Ccr below 1 % may be observed in the case o f 'S-type hyperamylasemia' [46].…”
Section: Diagnostic Proceduresmentioning
confidence: 99%